Understanding compliance in programs promoting conservation agriculture: Modeling a case study in Malawi - Ward, Patrick S.; Bell, Andrew R.; Droppelmann, Klaus; Benton, Tim (International Food Policy Research Institute, 2016)
Land degradation and soil erosion have emerged as serious challenges to smallholder farmers throughout southern Africa. To combat these challenges, conservation agriculture (CA) is widely promoted as a sustainable package of agricultural practices. Despite the many potential benefits of CA, however, adoption remains low. Yet relatively little is known about the decision-making process in choosing to adopt CA. This article attempts to fill this important knowledge gap by studying CA adoption in southern Malawi. Unlike what is implicitly assumed when these packages of practices are introduced, farmers view adoption as a series of independent decisions rather than a single decision. Yet the adoption decisions are not wholly independent. We find strong evidence of interrelated decisions, particularly among mulching crop residues and practicing zero tillage, suggesting that mulching residues and intercropping or rotating with legumes introduces a multiplier effect on the adoption of zero tillage.